(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Ophthalmalgia (eye pain) is of interest to various fields of medicine, and may be due to ocular or extra-ocular causes. Common ocular causes include glaucoma, ocular inflammatory disease (like keratitis, skleritis or neuritis), and orbital disease. Notable extra-ocular causes include trigeminal neuralgia, headaches of various types, intracranial vascular lesions, and otolaryngological inflammatory disorders. The diagnosis and management of patients with ophthalmalgia requires a multidisciplinary approach with contributions from ophthalmology, neurology, neurosurgery, oto(rhino)neurology, as well as other specialties.